2017
DOI: 10.2298/jsc161206039s
|View full text |Cite
|
Sign up to set email alerts
|

Zinc, copper and nickel complexes of a macrocycle synthesized from pyridinedicarboxylic acid: A spectroscopic, thermal and theoretical study

Abstract: The metal(II) ion complexes of a pentadentate macrocycle 1, namely 3,12-dioxa-6,9,18-triazabicyclo[12.3.1]octadeca-1(18),14,16-triene-2,13-dione are synthesized. This macrocycle is prepared from the reaction of dipotassium salt of 2,6-pyridinedicarboxylic acid with ethylenediamine and 1,2-dibromoethane. The reaction of 1 (L) in methanol with MCl 2 .xH 2 O gave complexes with the general formula [M(L)Cl 2 ] (where M= Ni(II) 2, Cu(II) 3 and Zn(II) 4, respectively). The analysis of IR, 1 Hand 13 C-NMR spectral da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…Thus, the DNA-binding activity is a preliminary test along with antimicrobial activity after synthesis and characterization of a metal-based complex destined for biological activities. 8 In the present study, a copper(II) complex related to the less commonly found polymeric type of paddlewheel ________________________________________________________________________________________________________________________ Available on line at www.shd.org.rs/JSCS/ (CC) 2020 SCS.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Thus, the DNA-binding activity is a preliminary test along with antimicrobial activity after synthesis and characterization of a metal-based complex destined for biological activities. 8 In the present study, a copper(II) complex related to the less commonly found polymeric type of paddlewheel ________________________________________________________________________________________________________________________ Available on line at www.shd.org.rs/JSCS/ (CC) 2020 SCS.…”
Section: Introductionmentioning
confidence: 68%
“…This type of activity was observed for some other copper(II), nickel(II) and zinc(II) complexes derived from a pentadentate macrocyclic ligand. 8 The reference complexes were active against some microbial strains but their activity was ________________________________________________________________________________________________________________________ Available on line at www.shd.org.rs/JSCS/ (CC) 2020 SCS.…”
Section: Antifungal Studiesmentioning
confidence: 99%